The correlation between serum creatinine and burn severity and its predictive value: Correlation between serum creatinine and burn severity - Shao, Huawei; Ni, Liangfang; You, Chuangang; Li, Qiong; Mao, Shulei (Cellular and Molecular Biology, 2023)
This study aimed to explore the correlation between serum creatinine and burn severity and the value of predicting the outcome of patients. For this purpose, a total of 268 burn patients (BUP) were collected. According to the burn area, they were divided into mild group (MIG) (n = 125, burn area 30% - 49%), moderate group (MOG) (n = 80, burn area 50% - 79%) and severe group (SEG) (n = 63, burn area ≥ 80%). According to the prognosis, they were divided into survival group (SUG) (n = 170) and death group (DEG) (n = 98). At the same time, the control group (COG) was selected from the physical examination center of our hospital. 5 mL of fasting venous blood was collected from all BUP on the first, seventh, 14th and 21st days after admission. 5 mL of fasting venous blood was collected from the COG. Creatinine (CRE) level was measured by enzyme method. Cholinesterase (CHE) level in serum was measured by improved Ellman method. The changes of CRE and CHE in serum were compared among all groups to explore the correlation between serum creatinine and burn severity and its prediction Measure the value of patients' outcomes. Results showed that except for the first day after burn, the level of serum CRE in BUP was raised than that in the COG, and the level of serum CHE in BUP was reduced than that in the COG (P<0.05). The serum CHE level of BUP in all groups increased at first and then decreased, and the highest level was on the first day after injury. At the same time, the level of CRE in SEG was raised than that in MIG and MOG, and the level of CRE in MOG was raised than that in MIG (P<0.05). The serum CHE level of BUP in all groups decreased at first and then increased, and the lowest level was on the first day after injury. At the same time, the level of CRE in SEG was reduced to that in MIG and MOG, and the level of CRE in MOG was reduced to that in MIG (P<0.05). The level of CRE in serum of BUP in both groups increased at first and then decreased, and the level was the highest on the first day after injury. At the same time, the level of CRE in the DEG was raised than that in the SUG (P<0.05). The level of CHE in serum of BUP in both groups decreased at first and then increased, and the level was the lowest on the first day after injury. At the same time, the level of CRE in the death group was reduced than that in the SUG (P<0.05). Logistic regression analysis showed that there was statistical significance in the regression coefficients on the 1st, 7th, 14th and 21st day after burn, and on the 1st and 21st day after-burn. ROC curve analysis shows that CRE and CHE have certain value in diagnosing the prognosis of BUP, and the diagnostic value of CRE is higher. Cre level increases with the aggravation of burn patients, and ChE level decreases with the aggravation of BUP. In conclusion, Cre and ChE have certain value in diagnosing the prognosis of BUP and can be widely used in clinical practice.